Diabetes among Indigenous Orang Asli adults in Peninsular Malaysia: Prevalence and associated factors from Orang Asli Health Survey 2022 - Hasimah Ismail; Thamil Arasu Saminathan; Hamizatul Akmal Abd Hamid; Wan Kim Sui; Tania Gayle Robert Lourdes; Noor Ani Ahmad (PLoS ONE, 2026)
Background Type 2 diabetes mellitus (T2DM) is a growing public health problem globally, and in Malaysia. Orang Asli, the Indigenous population in Peninsular Malaysia, often experience a disproportionate burden of diabetes, driven by social disadvantage, lifestyle transitions, and limited access to healthcare. Given that no nationwide diabetes assessment has been conducted among this under-represented group, this study therefore aimed to determine the prevalence of diabetes and its associated factors among Orang Asli adults in Peninsular Malaysia. Methods The Orang Asli Health Survey (OAHS) 2022 was a nationwide cross-sectional survey with a complex sampling design conducted among Orang Asli adults living in non-institutional households across nine states of Peninsular Malaysia. A two-stage stratified sampling strategy was used, with locality (urban, fringe, remote) as the primary stratum and tribe (Senoi, Proto-Malay, Negrito) as the secondary stratum. Data were collected using structured interviewer-administered questionnaires and standardised clinical measurements. Diabetes was defined as self-reported physician-diagnosed diabetes or fasting blood glucose ≥7.0 mmol/L. Descriptive statistics, chi-square tests, and multiple logistic regression were performed using SPSS Version 20, accounting for the complex survey design. The adjusted odds ratios (AORs) and 95% confidence intervals (CIs) were reported. Results A total of 9,206 Orang Asli adults participated in the diabetes module. The overall prevalence of diabetes was 16.1% (95% CI: 14.3–17.9). Diabetes prevalence was higher among the females (16.8%), those aged ≥60 years (28.1%), urban residents (21.1%), Proto-Malay (18.8%) and Senoi (14.0%) tribes, participants with no formal or incomplete primary education (19.1%), those with monthly household income ≥RM2000 (21.2%), obese individuals (21.1%), respondents with hypertension (24.2%) and those with high total cholesterol (21.7%). In multivariable analysis, diabetes was significantly associated with age 40–59 years (AOR 1.64; 95% CI: 1.35–1.99) and ≥60 years (AOR 2.14; 95% CI: 1.40–3.28), urban (AOR 1.73; 95% CI: 1.07–2.79) and fringe (AOR 1.63; 95% CI: 1.13–2.35) localities, Senoi (AOR 1.70; 95% CI: 1.08–2.68) and Proto-Malay (AOR 2.41; 95% CI: 1.50–3.86) tribes, incomplete primary education (AOR 1.28; 95% CI: 1.02–1.60), household income ≥RM2000 (AOR 1.47; 95% CI: 1.12–1.93), hypertension (AOR 1.42; 95% CI: 1.03–1.95) and hypercholesterolemia (AOR 2.17; 95% CI: 1.70–2.76). Conclusions Diabetes is common among Orang Asli adults in Peninsular Malaysia. Older age, urban and fringe residence, specific tribal groups, lower education, higher income, hypertension, and hypercholesterolaemia were associated with diabetes. These findings highlight the need for culturally appropriate diabetes prevention, screening, and management strategies tailored to Orang Asli communities, particularly for the elder subgroup and those living in urbanised settings.